Pengaruh Gaya Kepemimpinan dan Motivasi Berprestasi terhadap Kinerja Pegawai Dinas Kebudayaan dan Pariwisata Kota Pekanbaru - Alfiandri Alfiandri (Universitas Riau, 2010)
Leadership is important rule in motivating official in order them to becoming euthusiasmfor work. Effect of euthusiasm for work will be can doing official performance at the high level. Thepurpose of this research is to know effect of leadership style and achievement motivation toofficial performance at Culture and Tourism Departement Pekanbaru City. The research populationare official Culture and Tourism Departement Pekanbaru City are fourty people. All population istaking sample or census method. To obtain data and information the research conducted a surveyand interview depth. Data analysis is using multiple regression corelative. The research resultfounded that effect leadership style as a partial done not to official performance significantly buteffect leadership style and achievement motivation all the as same as it was influence to officialperformance positively and significantly